The Concept of Islamic Justice During the Umayyad Dynasty - Riska Rosidah (Al-Mahkamah: Islamic Law Journal, 2024)
Justice in Islam is very important, to realize justice and welfare and as an effort to protect the rights and obligations of individuals, groups and society as a whole, this is in accordance with the principles and objectives of Islamic law itself. With the existence of Islamic justice, the freedom of each individual is protected, the equality of every individual's rights before the law and in social life is maintained, and social security for every individual and society can be realized.Based on the purpose of, the implementation of Islamic justice as a forum for implementing or carrying out the laws of Allah SWT and uniting Allah SWT, it can be concluded that the implementation of Islamic justice is worship. However, it does not mean that everyone can become a judge as a court implementer because there could be mistakes if the position of judge is not carried out by knowledgeable people.As a note, every judicial administrator is free from the interests of the ruler and the influence of political interests. It was different during the time of al-Khulafa Al-rasyidin, a Caliph who directly held the court and acted as a Judge. Where the Umawiyyah Era was the era of the rise of patriarchy in the realm of government. Islam which is relatively widely spread abroad is not accompanied by good internal system management. At this stage, the social institutions that have been built cannot all be realized, because there will always be conflicts that hit. As a consideration, every period of government in a nation and country. Leadership must uphold a law. Thus, when we uphold a law properly as the foundation of the strength of the nation and country or even a monarchy government will bring peace, justice and welfare.